Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.